ANALISIS SOSIAL EKONOMI MASYARAKAT TERHADAP BERTAMBAHNYA LAHAN TIDUR DI DESA TARAITAK KECAMATAN LANGOWAN UTARA - Rizki E. Wowiling; Mex F.L. Sondakh; Theodora M. Katiandagho; Eyverson Ruauw (COCOS, 2014)
ABSTRACTRizki Efraim Wowiling. Communities Socio Economic Analysis of the Increase of UnusedLand in Taraitak Village, North Langowan Sub District (under the guidance of Mex. F. L.Sondakh as a chairman, Theodora. M. Katiandagho dan Eyverson Ruauw as members)Land is a very important factor in the production of agricultural activities. Land which isnot cultivated or uncultivated land which is called unused land will affect the income of farmersand will have an impact on the decrease of production. This study aims to identify socioeconomicfactors that lead to increased of unused land in Taraitak village.The method of data collection was done by using primary data and secondary data.Primary data obtained from interviews with respondents using a questionnaire that has beenprepared, while the secondary data obtained from the office of the village associated with thisresearch.The research result showed that there were socio-economic factors influence the increaseof unused land. The social factors were low education of farmers and farmer attitudes that hardto be opened to the development of agriculture, lack of human resources, capabilities and less ofagriculture knowledge. Economic factors were land owners do not have enough capital to runtheir farm.Key Word : Unused Land, Factor Socio Economic.